Analysis and statistical modeling of copper ions biosorption onto calcined chicken eggshell - Marković Miljan; Gorgievski Milan; Štrbac Nada; Grekulović Vesna; Zdravković Milica; Marković Marina; Stanković Dalibor (Journal of the Serbian Chemical Society)
The study on the possible use of calcined chicken eggshells as a biosorbent for copper ions removal from aqueous solutions, as well as some comparisons between raw and calcined eggshells, are presented in this paper. SEM- -EDS and FTIR analysis of the calcined chicken eggshell samples were performed. In addition, the DTA-TGA analysis on raw chicken eggshells was performed. The influence of various process parameters, such as solution pH, stirring rate, biosorbent mass and Cu2+ concentration, was investigated. The kinetic analysis using four different empirical kinetic models was performed. The equilibrium analysis was done using the Langmuir, Freundlich and Temkin isotherm models. The process was optimized using the response surface methodology based on the Box–Behnken design (RSM-BBD). The obtained results are compared to our previous study on raw eggshells as a biosorbent for Cu2+ removal, in order to determine the justification for biosorbent modification (i.e., the calcination of raw eggshells).